The Use of Communicative Language Teaching to Improve Students’ Participation and Vocabulary Achievement at Junior High School - Muhammad Nurul Fahmi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
ents’ participation and vocabulary achievement in one of junior high schools in jember (MTS Unggulan Al-Qodiri 1 Jember). Based on the preliminary study, it was found that the eight grade students had problem with vocabulary achievement and their participation during learning process. This issues showed on the result of interview in the preliminary study, where the english teacher explained that most students of an eight-grade class (VIII D) failed to understand the meaning of the words and they also felt confused on how to use words in senteces. Besides, their participation during learning process was categorized as passive. The action was conducted in two meetings. During the implementaion of the action, the researcher collaborated with the english teacher taught vocabulary with using communicative language teaching as the method and observed students development during learning process in both meetings. Then, the researcher administrated vocabulary test in third meeting with aims to measure students’ vocabulary achievement after learning by using CLT. The findings of this research revealed that the use of communicative language teaching could help eight-grade students improving their participation and vocabulary achievement. This was proven by the result of the observation during vocabulary learning process with precentage 68% (meeting 1) and 73% (meeting 2) of students categorized as active particpation. Then, the result of the vocabulary test also being evidence if the use of CLT could improve students’ vocabulary achievement, where 19 students (73%) achieved the minimum scores (70).
Reupload Repository Maya 26 Maret 2026
Keywords: Communicative Language; Improve Students; Participation and Vocabulary Achievement